2018
DOI: 10.1111/plar.12241
|View full text |Cite
|
Sign up to set email alerts
|

She's Come Undone: Parsi Women's Property and Propriety under the Law

Abstract: Parsis (Indian Zoroastrians), like many religious groups, manage their ritual spaces and funds with charitable trusts. High numbers of intermarriage have caused much debate over who counts as a Parsi within the community, and more attention is being paid to women and their rights of access. After a local trust in Valsad, Gujarat, barred intermarried women from entering Zoroastrian sacred spaces, Goolrukh Gupta, an intermarried Parsi woman, sued her trust in the high court. It ruled that Gupta was no longer a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Legal historian Mitra Sharafi (2014), has extensively shown how keenly and frequently Parsis have turned to the courts to solve their internal disputes and protect and even form their communal identity historically. 16 My ethnographic research in contemporary Mumbai confirmed this pattern, as a large number of my interlocutors were parties in civil disputes especially over rights to communal, trust-managed properties (Vevaina, 2018). Legal activism is also commonly taken up by a few individuals, like Farhad and Sukhadwalla, who have the legal knowledge or assistance to pursue a case in court, infamous in India to be expensive as they often run for many years.…”
Section: Seeking a Writmentioning
confidence: 79%
See 1 more Smart Citation
“…Legal historian Mitra Sharafi (2014), has extensively shown how keenly and frequently Parsis have turned to the courts to solve their internal disputes and protect and even form their communal identity historically. 16 My ethnographic research in contemporary Mumbai confirmed this pattern, as a large number of my interlocutors were parties in civil disputes especially over rights to communal, trust-managed properties (Vevaina, 2018). Legal activism is also commonly taken up by a few individuals, like Farhad and Sukhadwalla, who have the legal knowledge or assistance to pursue a case in court, infamous in India to be expensive as they often run for many years.…”
Section: Seeking a Writmentioning
confidence: 79%
“…This management was consolidated in establishing the Bombay Parsi Punchayet (BPP), a trust and the legal mechanism for managing much Parsi sacred space in the city. This form of communal management has become critically important in Parsi governance and spatial politics in the city (Vevaina, 2018).…”
Section: “Apri Bombay” Our Bombay1mentioning
confidence: 99%
“…The settlement and trust were such instruments, and it is this perhaps implicit entanglement of kinship and property that emerged in much of my research with Parsis in Mumbai. 15 English women's property was held under coverture through the nineteenth century, yet these laws were never transferred over to the Indian colony explicitly. Indian marriage laws were governed and amended through a variegated history of personal laws.…”
Section: Coverture: the Veiled Womanmentioning
confidence: 99%
“…In her ethnographic study of Parsi property law, Leilah Vevaina (2018) describes how compositional identities are construed in relation to property rights, and in particular are defined through contextualized membership claims. Likewise, Boulder MHC residents argued that it was through their housing, regardless of its age or condition, that their community membership was solidified.…”
Section: Security Investment and Belonging: Mh Ownership In Bouldermentioning
confidence: 99%